Islam and morality : a philosophical introduction - Leaman, Oliver, 1950- (London: Bloomsbury Academic, 2019)
'Islam and Morality considers how Islam, the Qur'an, and other Islamic texts have approached the ethics of a variety of contemporary and historical issues. Oliver Leaman provides a varied, balanced, and thought-provoking account of how Islamic thinkers discussed medical ethics, wealth, poverty, the environment, and law. He explores the work of a range of Islamic thinkers, including Rumi, Ibn al-'Arabi, al-Ghazali, Mutahhari and Barlas, while taking into consideration the different branches of Islam and Islamic theology and law. The book also considers how Islam understands the concept of free will, the relationship between good and evil, and far less abstract topics like what we should eat and drink. Aimed at upper level undergraduates, postgraduates, and researchers working in Islamic Studies and ethics, this is one of the first books to provide a sustained reading of the importance of ethics within Islam'--
Justice -- Conflict -- Sins -- Health -- Bodies -- Nature -- Choice -- Sufis -- Principles.
Record to be deleted.
Keywords: Islamic ethics